Long-term trends in the number of Whooper Swans Cygnus cygnus breeding and wintering in Sweden - Nilsson, Leif (Wildfowl, 2014)
The Whooper Swan Cygnus cygnus was a rare breeding species in Sweden during the early years of the 20th century, when total numbers likely consisted of only 20 pairs. Recent decades have however seen a marked increase in numbers and a spread in the swans’ distribution, with the number of pairs breeding in the two northernmost provinces rising from 310 to 2,700 pairs between two main surveys, in 1972–75 and 1997. This paper documents continued long-term (1967–2014) increases in numbers of Whooper Swans breeding and wintering in Sweden, based on data collected by the Swedish Bird Monitoring Programme and during the mid-winter International Waterbird Counts (IWC). Most recent estimates for the country indicate that there are now 5,400 breeding pairs during the summer and close to 10,000 individuals present in normal or mild winters.